2022
DOI: 10.1002/aic.17569
|View full text |Cite
|
Sign up to set email alerts
|

Separation of He/N2/CH4 ternary mixtures by a triple‐reflux pressure swing adsorption process

Abstract: Conventional pressure swing adsorption (PSA) processes can only produce one high purity product in a single stage, whereas the state-of-art dual-reflux PSA (DR-PSA) can produce two high purity products simultaneously. However, multicomponent gas separation is often required in the industry, targeting at recovering several valued products at the same time. In this study, we propose a novel adsorption process, namely triple-reflux PSA (TR-PSA), to separate three components simultaneously. A middle product outlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Two-stage scale-up adsorption processes have been carried out at a coal mine site. A dual-reflux pressure swing adsorption (DR-PSA) process has been reported on the separation of binary gas mixtures. Based on the DR-PSA process, Guo et al proposed the triple-reflux pressure swing adsorption (TR-PSA) for the separation of the He/N 2 /CH 4 mixture. Yang et al and Qu et al investigated the VPSA process with a CO 2 displacement step to recover low-grade coalbed methane based on the principle of displacement chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…Two-stage scale-up adsorption processes have been carried out at a coal mine site. A dual-reflux pressure swing adsorption (DR-PSA) process has been reported on the separation of binary gas mixtures. Based on the DR-PSA process, Guo et al proposed the triple-reflux pressure swing adsorption (TR-PSA) for the separation of the He/N 2 /CH 4 mixture. Yang et al and Qu et al investigated the VPSA process with a CO 2 displacement step to recover low-grade coalbed methane based on the principle of displacement chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…May et al investigated the separation of CH 4 and N 2 using dual-reflux PSA with activated carbon, Engelhard titanosilicate type 4 (ETS-4), and ionic liquidic zeolites as adsorbents via experiments and simulations. Results showed that optimized DR-PSA processes using Norit RB3 adsorbents can upgrade dilute methane (2.4%) to 35.7%, leaving a clean nitrogen vent bearing 3000 ppmv methane, which is promising in the reduction of fugitive methane emissions. Guo et al employed a triple-reflux strategy to separate CH 4 /N 2 /He by opening a third channel on DR-PSA and achieved three high-purity streams simultaneously. Rodrigues and Li et al used a more adsorptive component (CO 2 ) to displace adsorbed CH 4 and achieved a 75% CH 4 product with 89% recovery from 10% CH 4 . , Recently, Li et al employed a pure methane displacement strategy to achieve 99% CH 4 from 10% CH 4 using simulated moving beds …”
Section: Introductionmentioning
confidence: 99%
“…23−25 Results showed that optimized DR-PSA processes using Norit RB3 adsorbents can upgrade dilute methane (2.4%) to 35.7%, leaving a clean nitrogen vent bearing 3000 ppmv methane, which is promising in the reduction of fugitive methane emissions. Guo et al employed a triple-reflux strategy to separate CH 4 /N 2 /He by opening a third channel on DR-PSA 26 neously. Rodrigues and Li et al used a more adsorptive component (CO 2 ) to displace adsorbed CH 4 and achieved a 75% CH 4 product with 89% recovery from 10% CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, multicomponent gas separation with the aim of recovering several valuable products simultaneously is emphasized in industrial applications. 20 In the present study, we designed a newly developed state-of-the-art dual membrane system, including carbon nitride and graphdiyne, for recovering helium from ternary mixtures of He/N 2 /CH 4 . Given the challenging duties and costs of conducting experimental tests as well as focusing on the importance of a molecular-based outlook, the computational methods can be carried out as an alternative route for modern scientific research activities.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In other words, natural gas, which mainly consists of methane (CH 4 ), is the sole feasible source of helium with an appropriately high concentration for commercial purposes. 5,20 In addition to methane and helium, natural gas contains other hydrocarbons (C 2+ ), carbon dioxide (CO 2 ), nitrogen (N 2 ), water vapor, and a small amount of hydrogen sulfide (H 2 S). 3,21 In a typical natural gas process, undesirable components such as CO 2 , H 2 S, H 2 O, and C 2+ are required to be removed first from raw natural gas.…”
Section: Introductionmentioning
confidence: 99%